1990
DOI: 10.1021/ic00329a013
|View full text |Cite
|
Sign up to set email alerts
|

Two-electron oxidation of cobalt phthalocyanines by thionyl chloride. Implications for lithium/thionyl chloride batteries

Abstract: large molecules at low temperature (ca. 225 K) and much smaller oligocadmium molecules at high temperature (ca. 340 K).3. The Ii3Cd and 13C NMR spectra are consistent with vertex-linked adamantanoid cages as the structure type for the aggregates in solution. The postulated aggregate structures in SOlution are fragments of the known crystal structures. 4. The low ionic conductivity and the 'I3Cd NMR data indicate that some ligand disproportionation occurs in solution, such that the larger oligoadamantanoid aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 1 publication
2
26
0
Order By: Relevance
“…The broadness may reflect incipient splitting in the lower symmetry of these species. The peak at 530-570 nm is a T--rr transition in the mononuclear species, similar to previous assignments of related species (13,14,18,20,21).…”
Section: ( I ) Tbtap(c)h2supporting
confidence: 88%
“…The broadness may reflect incipient splitting in the lower symmetry of these species. The peak at 530-570 nm is a T--rr transition in the mononuclear species, similar to previous assignments of related species (13,14,18,20,21).…”
Section: ( I ) Tbtap(c)h2supporting
confidence: 88%
“…32,33 Because of different oxidation states of CoPc and TiOPc, there is a growing interest about the CoPc and TiOPc complexes. 34−36 Despite this, studies of the electrochemical properties of CoPc and TiOPc are still rare in the literature.…”
Section: −29mentioning
confidence: 99%
“…[15][16][17][18] The mechanism of the reduction of SOCl 2 by CoPc has been demonstrated by Doddapaneni and Bernstein. 15,16 Bernstein has shown the formation of the adduct CoPc•SOCl 2 is the ratecontrolling step in this catalytic reduction reaction, followed by a rapid electron transfer process, the adduct CoPc•SOCl 2 accepts the electrons. S, SO 2 and Cl -leave, and CoPc is returned.…”
Section: Electrocatalytic Activity Of Copc/mwcnts To Li/socl 2 Batterymentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23] Among these works, using macromolecular compounds, especially metal phthalocyanine (MPcs) compounds acting as catalyst attracted much interest. [14][15][16][17][18][19][20] It has been demonstrated that the assemblies of CNT-based MPcs have shown outstanding performance in the fields of solar energy conversion, electrochemical sensor and catalysis. [24][25][26][27] However, functionalizing MPcs onto the surface of CNTs is of great difficulty.…”
Section: Introductionmentioning
confidence: 99%